EFEKTIVITAS PENGGUNAAN MULTIMEDIA INTERAKTIF PADA MATERI DIMENSI TIGA - Syukria, Arina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
This study examines the use of interactive multimedia that can be effectively used in the learning process on the three dimensional material, to answer this problem, the research uses data collection techniques with teacher ability observation sheet, student activity observation sheet, test of learning result, and student response questionnaire. Data processing in this study using simple statistics with percentage and t-test. Achievement of the effectiveness of learning by using interactive multimedia is based on; the ability of teachers to manage learning, student activities during learning, student responses to learning and learning mastery. From the results of this study found that, the use of interactive multimedia effectively used in learning on the material dimension three in class X SMA 3 Banda Aceh. This is shown from the aspect of the ability of the teacher to manage the learning that is in the good category that is the score 4.13, the completeness of learning outcomes by 80% and student response results that show more than 90% of students interested in the appearance of illustration / interactive multimedia images and are interested to follow further learning. So it can be concluded the use of interactive multimedia, effectively used in learning on the material dimension three in class X SMA Negeri 3 Banda Aceh.